Junkyard Dogs: Walt Longmire #6 - Johnson, Craig, 1961- (New York : Viking, 2010)
After a severed thumb turns up at the dump outside of Durant, Wyoming, Sheriff Walt Longmire ignores the fact that someone has claimed it. He needs a mystery to keep Deputy Santiago Saizarbitoria, whos suffering from bullet fever, on the job until he can think of a way to keep him from quitting. Its just that sort of kindness that defines Longmire, whose unwillingness to assume the worst leads to him getting pepper-sprayed, bit in the ass, and very nearly shot. Like any good mystery, this depends less on the plot than its depiction of interesting people in an interesting place. But, as the story ambles along, with Walt taking a lot of ragging from the people who work for him (including exPhilly cop and love interest Victoria Moretti), the severed thumb points the way through a surprisingly twisty mystery that involves junkmen, land developers, and a creepy ex-convict. And, as he proved in last years terrific Dark Horse, Johnsona born storyteller if ever there was onecan do one helll of a set piece in a snowstorm (even with a limping, overweight sheriff). Longmire may be contemplating early retirement, but readers will demand that he serve out his full term of serviceand run for reelection.
Keywords: Longmire, Walt (Fictitious character) -- Fiction; Sheriffs -- Fiction; Wyoming -- Fiction; Mystery fiction